A Critical Stylistic Analysis of the Song Lyrics Sedih Hati (Jurnal Bahasa, 2025)
The beauty of a song is revealed not only through its musical arrangement but also through the implicit meanings embedded within its lyrics. The aesthetic appeal and communicative force of lyrics are shaped by elements such as metaphor, repetition, symbolism, and tropes. This study was conducted to identify the linguistic strategies employed by Malique in the lyrics of Sedih Hati in terms of meaning construction and their effects on listeners, particularly from the perspectives of rhetoric, semantic structure, and lexical choice, using the critical stylistics framework proposed by Lesley Jeffries (2010). The findings of this study show that all the linguistic strategies identified within the framework were present in the lyrics analysed. Through the application of Jeffries’ theory, the linguistic features used by Malique not only demonstrate artistic creativity but also reveal the presence of critical social messages related to oppression, injustice, and societal anxiety, as reflected through cynical metaphors, political satire, and representations of social stratification in the lyrics. This study broadens the understanding of local music stylistics by illustrating how Malaysian rap lyrics function as a valuable medium of social critique and it affirms that rap lyrics, particularly those by Malique, possess significant literary value and merit scholarly attention in language studies.Keywords: content analysis, song lyrics, critical stylistics, figurative language, social messages, local musicFull text: PDF